We have to solve x^4 - 3x^2 + 2 = 0

x^4 - 3x^2 + 2 = 0

=> x^4 - 2x^2 - x^2 + 2 = 0

=> x^2(x^2 - 2) - 1(x^2 - 2) = 0

=> (x^2 - 1)(x^2 - 2) = 0

x^2 = 1

=> x = 1 , x = -1

x^2 = 2

=> x = sqrt 2, x = -sqrt 2

**Th solutions of the equation are (-sqrt 2, -1, 1, sqrt 2)**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now